IFC Financials and Projects 2014 : Big Challenges, Big Solutions - International Finance Corporation (Washington, DC: World Bank Group, 2014)
International Finance Corporation (IFC or the Corporation) is the largest global development institution focused on the private sector in developing countries. Established in 1956, IFC is owned by 184 member countries, a group that collectively determines its policies. IFC is a member of the World Bank Group (WBG)1 but is a legal entity separate and distinct from IBRD, IDA, MIGA, and ICSID, with its own Articles of Agreement, share capital, financial structure, management, and staff. Membership in IFC is open only to member countries of IBRD. At the 2013 Spring Meetings, the WBG adopted two ambitious goals: to end extreme poverty by 2030 and to boost shared prosperity for the poorest 40 percent in developing countries. At the Annual Meetings in October 2013, the Board of Governors approved the first strategy for the WBG focused on delivery of transformational solutions, marshaling combined resources more effectively, and accelerating collaboration with the private sector and our development partners. IFC s strategic focus areas are: strengthening the focus on frontier markets; addressing climate change and ensuring environmental and social sustainability; addressing constraints to private sector growth in infrastructure, health, education, and the food-supply chain; developing local financial markets; and building long-term client relationships in emerging markets.